Performance Analysis of Identifier Locator Communication Cache Effects on ILNPv6 Stack - Kadi, Mohsen; Suleiman, Maher; Jammoul, Samih (Journal of Computer Networks and Communications, 2021)
Identifier-locator network protocol (ILNP) is a host-based identifier/locator split architecture scheme (ILSA), which depends on address rewriting to support end-to-end mobility and multihoming. The address rewriting is performed by hosts using a network layer logical cache that stores state information related to the communicated hosts, which is called identifier-locator communication cache (ILCC). Since address rewriting is executed on a packet basis in ILNP, ILCC lookups are required at each packet reception and transmission. This leads to a strong correlation between the host’s network stack performance and ILCC performance. This paper presents a study of the effect of ILCC size on network stack performance. Within this paper, a direct comparison of the performance of two ILNP prototypes that differ by ILCC management mechanism is conducted. We present ILCC size measurements and study their effects on the host’s network stack performance. The results show that ILCC growth caused by correspondents increase has a significant effect on the latency of both network and transport layers. The obtained results show that controlling ILCC size through an effective policy strongly enhances ILNP network stack performance.